O olhar da criança a partir das telas do cinema : memórias e educação - Silva, Ana Cristina Vieira e (2019)
This research “The Child's View from the Screens of the Movie Theater: Memories and Education" was developed during the Master’s degree in the graduation Program in Education at the Federal University of Mato Grosso. Its theme discusses cinema as an educational tool, as well as a tool for developing one’s role in the society, bringing out memories of children and teenagers, who participate in a social and religious Project Cáritas in Várzea Grande. In this study, based on research and phenomenology, we presented film sessions to 30 children between 9 and 13 years old, whom were residents of two different neighborhoods: 7 de Maio and Eliane Gomes. These sessions were followed by conversation sessions, in which we observed their impressions and how cinema reflected in each child's life. We divided the research into four chapters: in the first, we talk about its methodological path; in the second, we present the institutions Caritas Internationalis, Cáritas Brasileira and its branches in the state of Mato Grosso, and Cáritas de Várzea Grande; in the third, we discuss concepts of childhood, the child in a situation of vulnerability, bringing up his/her history; in the fourth, we describe the children's particular stories and their impressions about it, also reaching the school environment through interviews with teachers and principals, to understand the multiple relationships that the child establishes with his/her environment. In the final considerations, we return to important points and reflect about the dialogue and the experience that cinema can provide us. To develop the theoretical and methodological discussions, we based ourselves on Benjamin (1994), Bosi (1994), Halbwachs (2006), Ricouer (2007), Fresquet (2017), Del Priore (2007), Kramer Incontri (1997), Freire (1987), among others.